Pengembangan Modul Pembelajaran Matematika Materi Limit Fungsi Aljabar Berbasis Discovery Learning Disertai Nilai-Nilai Islam - Fransiska Yulianto; Jazim Ahmad; Rahmad Bustanul Anwar (Absis: Mathematics Education Journal, 2022)
This study aims to produce a mathematics learning module on the material limit of algebraic functions based on Discovery Learning accompanied by valid and practical Islamic values. This study uses the ADDIE research method (Analyze, Design, Development, Implementation, Evaluation). The object of this research is the mathematics learning module on the material limit of algebraic functions. The subjects of this study were students in class XI MIA of state senior high school 1 South Rawajitu. This study's data collection techniques used a validation questionnaire of material experts, media experts, Islamic values experts, and student practicality test questionnaires. Based on the results of the validation carried out on the mathematics learning module on the material limit of algebraic functions based on Discovery Learning with Islamic values obtained valid and very practical results with an average percentage of validity test results of 77.8% and an average percentage of practicality test results of 84.6%.